2015
DOI: 10.1002/ente.201500358
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Carbon–Metal Fluoride Nanocomposites for Lithium‐Ion Batteries

Abstract: Metal‐fluoride‐based conversion materials have gained interest as cathode materials for lithium‐ion batteries due to their high theoretical energy densities. However, metal fluorides are electrically insulating and experience large volume changes during the charge and discharge processes. Effective synthesis of carbon–metal fluoride nanocomposites (CMFNCs) with stable morphology is one of the keys to achieve high capacities with sustainable cycle life. A general method for the synthesis of CMFNCs is described … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…The galvanostatic charge/discharge profiles of the CoF 2 nanoparticles from decomposition of Co(AMD) 2 in [BMIm][BF 4 ] are presented in Figure . The redox plateau at the first discharge is 1.8 V, which is much lower than the theoretical value but comparable to that reported in the literature . Two oxidation plateaus in the charge process are in the potential ranges of 3.5 to 4.2 V and 4.2 to 4.8 V, which correspond to the processes of reconverting back into Co x F and CoF 2 , respectively .…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…The galvanostatic charge/discharge profiles of the CoF 2 nanoparticles from decomposition of Co(AMD) 2 in [BMIm][BF 4 ] are presented in Figure . The redox plateau at the first discharge is 1.8 V, which is much lower than the theoretical value but comparable to that reported in the literature . Two oxidation plateaus in the charge process are in the potential ranges of 3.5 to 4.2 V and 4.2 to 4.8 V, which correspond to the processes of reconverting back into Co x F and CoF 2 , respectively .…”
Section: Resultssupporting
confidence: 76%
“…The redox plateau at the first discharge is 1.8 V, which is much lower than the theoretical value but comparable to that reported in the literature. [58][59][60] Twoo xidation plateausi nt he chargep rocess are in the potential ranges of 3.5 to 4.2 Vand 4.2 to 4.8 V, which correspond to the processes of reconvertingb acki nto Co x Fa nd CoF 2 ,r espectively. [58] In the second discharge process, the slopep rocess before the plateau at 1.5 Vc an be assigned to the reduction of Co x F with lithium ions.…”
Section: Electrochemical Measurementsmentioning
confidence: 99%
“…The PbF2-based compounds exhibit fluoride ion conductivity [18][19][20][21]; therefore, PbF2 was selected as an active material for the fluoride shuttle battery (FSB). It has been reported that the high adhesion state with carbon improved the charge and discharge capacities of metal fluorides for the active materials of LIBs due to the increased electronic conductivity [22][23][24][25][26][27][28][29][30][31][32]. This method can be used for the active material of the FSB.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Alternatively, chemical methods have been reported to synthesize CMNFCs, which showed much higher cycling stability. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] Recently, we have reported a facile method for the synthesis of carbon-metal uoride nanocomposites by reacting graphite uoride (CFx) with iron pentacarbonyl (Fe(CO) 5 ) at 250 C. [25][26][27] The C-FeF 2 nanocomposites obtained by this method delivered high reversible capacity in lithium half cells. 25,27 Further, pretreatment of the CFx precursor by mechanical milling has a signicant impact on the reversible capacity, which we attributed to the reduced particle size of CFx.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, the reaction occurs in one step and is quick (could be nished in 1 h). 27 Further, addition of conductive carbon is not required to prepare the electrodes. In this study, we used various uorinated carbon compounds namely, petro-coke, carbon black, graphite, and carbon-bers to synthesize C-FeF 2 nanocomposites.…”
Section: Introductionmentioning
confidence: 99%